Determination of the stability of a non-linear ordinary differential equation by least square approximation. Computational procedure - Benouaz, Tayeb; Arino, Ovide (Zielona Góra: Uniwersytet Zielonogórski)
The purpose of this paper is to present a computational procedure, based on the minimization in the least square sense, which is associated with a given non-linear ordinary differential equation, when considered in the neighborhood of one of its equilibrium points P, a linear ordinary differential equation, having the same stability property as the non-linear equation at P.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka